Juvenile Cellulitis in a Pup and its Management – A Case Report - G.E. Georgen; S.G. Sangeetha (The Indian Veterinary Journal, 2024)
A forty-five-day old female Dachshund pup was presented at TVCC, Mannuthy, KVASU with the history of nodules on different parts of the body which later broke up and developed to draining and erosive lesions within a period of 10 days. Clinical examination revealed submandibular lymphadenopathy, facial oedema and open exudative wounds in the ventral thorax, perianal and neck region. Impression smear and bacterial culture of the exudate showed negative results for bacterial involvement. The pup was successfully treated using tapering doses of prednisolone and cephalexin.